Influence of Seed Rate and Days of Pendimethalin Application on Weed Dynamics and Yield of Dry Direct Seeded Rice (Oryza sativa L.) - Bhattarai, Rajendra Kumar; Chaulagain, Bhimsen; Neupane, Reshama; Kaduwal, Sangita; KC, Bigyan; Bhandari, Aashray; Chand, Sweekriti; Shrestha, Jiban (Agronomy Journal of Nepal, 2025)
Dry Direct -Seeded rice is the sustainable alternative to the commonly transplanted rice that address the problems of water, labour and high production costs. However, the weed infestation causes heavy yield reduction in dry direct seeded rice (DDSR). The optimum seed rate and timing of pre-emergence herbicide application is also another crucial factors limiting production in DDSR.To evaluate optimum seed rate and days to pendimethalin application a field study was conducted in 2022 and 2023 in the experimental field of National Agronomy Research Centre, Khumaltar, Lalitpur, Nepal. The experiment was laid out in a split plot design with two seed rate (20 and 30 kg ha-1) assigned to main plot factor and five different days of pendimethalin application (1,2, 3 ,4 and 5 days after sowing of rice) was assigned to as sub plot factor. The treatment was experimented in four replications. The plot size was 3 × 4 m and spacing was 20 cm between row and sown continuously in line. The fertilizers were applied at the rate of 120: 40: 40 kg N: P2O5:K2O ha-1. The full dose of P2O5: K2O and one third dose of N was applied as basal. The remaining N was applied in two splits at tillering and booting stage. Observations in crop growth, weeds and yield and yield attributes were recorded. Seed rate of 30 kg ha-1 suppressed weeds efficiently and produced higher grain yield (7052 kg ha-1) compared with 20 kg recording less weed density and biomass. In the different days of pendimethalin application applying it on same day of sowing of rice resulted in better weed management and higher yield (7439 kg ha-1) compared with others days of it application.